2023
DOI: 10.1002/ldr.4790
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of satellite‐based rainfall product CHIRPS in estimating rainfall erosivity on the Loess Plateau

Abstract: Satellite‐based rainfall products have great potential for estimating rainfall erosivity, as they can provide continuous spatiotemporal distribution of precipitation estimates over large areas, especially for monitoring in areas with complex terrain and extreme climates. This paper uses the daily rainfall derived from the satellite‐based CHIRPS product on the GEE platform and Zhang's daily rainfall erosivity model to calculate the rainfall erosivity on the Loess Plateau during the period of 1981–2020. The accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Satellite remote sensing precipitation products have emerged as alternative sources of gauge observations in the past decade and have been widely utilized in mapping rainfall erosivity [26,27,[29][30][31][32]34,36]. Most studies have reported that these satellite products effectively capture the spatial distribution of rainfall erosivity [26,29,31,34], which is consistent with the results achieved in this study.…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…Satellite remote sensing precipitation products have emerged as alternative sources of gauge observations in the past decade and have been widely utilized in mapping rainfall erosivity [26,27,[29][30][31][32]34,36]. Most studies have reported that these satellite products effectively capture the spatial distribution of rainfall erosivity [26,29,31,34], which is consistent with the results achieved in this study.…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
“…Most studies have reported that these satellite products effectively capture the spatial distribution of rainfall erosivity [26,29,31,34], which is consistent with the results achieved in this study. However, the evaluation accuracy of rainfall erosivity magnitude derived from satellite products varies across studies, mainly due to differences in the satellite products used and the reference data employed in previous studies [26,29,31,34,36].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation